Matemáticas de formas de vida de agricultores do município de Santo Antônio da Patrulha - Oliveira, Sabrina Silveira de (Universidade do Vale do Rio dos Sinos, 2011)
This dissertation intends to study the language games used by farmers in the town of Santo Antônio da Patrulha when taking linear and surface measurements, by examining family resemblances and also the similarities they have with the language games used in mathematics as a school subject. The theoretical tools in this study stem from Ethnomathematics in its crossings with the theories of Michel Foucault and Wittgensteins ideas presented in his book Philosophical Investigations. The research data consists of interviews with two farming families, one of these farmers observations about his work activities, and the analysis of the first certificates of sale of real property issued in Santo Antônio da Patrulha. The analysis of this data suggests that markers associated with climatic conditions are present in the practices of planting and harvesting; farmers use the unit known as tamina in their linear and surface measurements; there were resistance movements during the imposition of the metric system in this town of southern Brazil; language games involving the use of the unit named tamina are learned through oral transmission and observation; and in the form of school life, such language games were /are not taught.
Keywords: Educação matemática; Etnomatemática; Unidades de medir superficie; Mathematics education; Ethnomathematics; Surface measuring units; ACCNPQ::Ciências Humanas::Educação